A method for preparing electrode material and supercapacitor application
The preparation of ZnCo2O4@NiOOH nanosheet electrode material by hydrothermal method solves the problems of low energy density and short cycle life of supercapacitors, and achieves high specific capacitance and excellent cycle stability. It is suitable for new energy storage and power grid applications.
Patent Information
- Application Number
- CN202411397993.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The low energy density and short cycle life of existing supercapacitors limit their application in the field of energy storage.
ZnCo2O4@NiOOH electrode material with heterostructured structure was constructed by hydrothermal method, and multiple hydrothermal reactions were performed using raw materials such as zinc nitrate, cobalt nitrate, urea and ammonium fluoride to prepare ZnCo2O4@NiOOH nanosheet electrode material to form a high specific capacitance and electrode materials with excellent cycle stability.
The energy density and cycle stability of supercapacitors have improved, making them have higher energy storage capabilities and longer service life in the energy storage field, and are suitable for use in new energy vehicles, communications and national power grids.
Smart Images

Figure CN118899173B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of capacitor electrode materials, and in particular to a method for preparing an electrode material and application of a supercapacitor. Background Art
[0002] The development of clean and renewable energy represented by wind power is a key measure to achieve "dual carbon". However, due to objective factors such as geography, environment and periodicity, most renewable clean energy has obvious intermittency. Therefore, it is imperative to develop advanced energy storage systems to effectively store these renewable energy sources. As a new type of energy storage device, supercapacitors not only have the unique characteristics of fast charging and discharging of capacitors, but also have the excellent energy storage efficiency of batteries. In addition, supercapacitors have broad application prospects in new energy vehicles, military, communications and national power grids due to their advantages such as good cycle life, fast responsiveness, good stability and high power density. Therefore, the development of high-performance supercapacitors is crucial.
[0003] Electrode materials are the core components of supercapacitors, mainly including carbon materials, transition metal oxides and conductive polymers. Among them, transition metal oxides are favored for their high specific surface area, high theoretical capacity, environmental friendliness and diverse composition. Its uniqueness lies in the variable valence metal elements that enable it to achieve efficient energy storage through highly reversible redox reactions. Compared with single metal oxides, bimetallic oxides have the advantage of two cations providing more active sites. In addition, bimetallic oxides have a conductivity far exceeding that of single metal oxides, and therefore exhibit better electrochemical energy storage performance than single metal oxides.
[0004] Bimetallic oxide zinc cobalt oxide materials have attracted widespread attention due to their unique structure and high theoretical specific capacitance. Bimetallic oxide zinc cobalt oxide materials have attracted widespread attention due to their unique structure and high theoretical specific capacitance. However, single transition metal oxide electrode materials have low energy density due to their weak conductivity, which limits their further application. Therefore, in order to improve the energy density and specific capacitance of zinc cobalt oxide nanomaterials, it is necessary to composite them with other materials to construct heterostructures to obtain high-performance electrode materials. Summary of the invention
[0005] In view of this, the present invention proposes an electrode material preparation method and supercapacitor application. The present invention constructs a heterogeneous structure ZnCo2O4@NiOOH electrode material synergistic effect by hydrothermal method to obtain excellent energy storage performance, effectively solving the problems of low energy density and short cycle life of existing energy storage devices.
[0006] The technical solution of the present invention is achieved in this way:
[0007] A method for preparing an electrode material comprises the following steps:
[0008] Zinc nitrate, cobalt nitrate, urea, ammonium fluoride and solvent are stirred and mixed, and then nickel foam is added. After a hydrothermal reaction, ZnCo2O4-loaded nickel foam is obtained. Nickel nitrate, ammonium fluoride and urea are mixed and then added to ZnCo2O4-loaded nickel foam. After a second hydrothermal reaction, the mixture is washed and dried to obtain an electrode material.
[0009] The electrode material preparation method comprises the following steps:
[0010] (1) Add zinc nitrate and cobalt nitrate to the solvent, perform magnetic stirring for 0.5 to 1 hour, then slowly add urea and continue stirring for 2 to 3 hours, then slowly add ammonium fluoride and continue stirring for 2 to 3 hours to obtain a mixed solution;
[0011] (2) adding the nickel foam and the mixed solution into a reactor for a hydrothermal reaction, then taking out and placing in an oven for reaction, collecting the nickel foam after the reaction is completed, washing, drying, and heat treating, thereby obtaining the nickel foam loaded with ZnCo2O4;
[0012] (3) Add nickel nitrate and urea into distilled water and stir magnetically for 0.5 to 1 h. Then add the loaded ZnCo2O4 nickel foam in step (2) into the reactor for a secondary hydrothermal reaction. After the reaction is completed, wash and dry to obtain an electrode material, which is recorded as ZnCo2O4@NiOOH nanosheet electrode material.
[0013] Furthermore, the zinc nitrate is Zn(NO3)2.6H2O; the cobalt nitrate is Co(NO3)2.6H2O; and the nickel nitrate is Ni(NO3)2.6H2O.
[0014] Furthermore, the size of the nickel foam is 15-30 mm×15-30 mm.
[0015] Furthermore, in step (1), the molar ratio of the zinc nitrate, cobalt nitrate, urea and ammonium fluoride is 1-5:1-5:1-10:0-10; the solvent is deionized water, and the ratio of the total mass of the zinc nitrate, cobalt nitrate, urea and ammonium fluoride to the volume of the solvent is 1.0-2.0 g:50 mL.
[0016] Furthermore, in step (2), the primary hydrothermal reaction temperature is 100-200°C, and the reaction time is 2-10 hours; the heat treatment temperature is 300-600°C, and the time is 2-10 hours.
[0017] Furthermore, in step (3), the mass ratio of nickel nitrate, urea and distilled water is 1:1-5:40-60; the temperature of the secondary hydrothermal reaction is 50-200°C and the time is 2-4h.
[0018] Furthermore, in step (1) and step (3), the stirring rate is 90-120 r / min.
[0019] Furthermore, in step (2) and step (3), the cleaning solvents are deionized water and anhydrous ethanol, and the number of cleaning times is 3 to 6 times; the drying temperature is 60 to 90° C., and the drying time is 12 to 24 hours.
[0020] The electrode material prepared by the preparation method of the present invention and the application of the electrode material in the preparation of supercapacitors.
[0021] Furthermore, the supercapacitor is an asymmetric supercapacitor, and its preparation process is as follows:
[0022] Activated carbon, acetylene black and polytetrafluoroethylene were uniformly mixed in a mass ratio of 6:3:1 to prepare the negative electrode, and then ZnCo2O4@NiOOH electrode material was used as the positive electrode, PVA-KOH gel was used as the electrolyte, the prepared positive and negative electrodes were separated by a separator, and finally encapsulated with an aluminum-plastic film.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention aims to improve the energy density and cycle stability of supercapacitor electrode materials to meet the needs of energy storage devices. The present invention uses common and low-priced Ni, Co and Zn as raw materials, prepares bimetallic oxide ZnCo2O4 nanosheets by hydrothermal method and heat treatment, and prepares ZnCo2O4@NiOOH nanosheet electrode materials by secondary hydrothermal method. The ZnCo2O4@NiOOH nanosheet electrode material prepared by this method has the characteristics of high specific capacitance, good energy density and excellent cycle stability, making it an ideal energy storage device, and the prepared supercapacitor has good specific capacitance and excellent pseudocapacitance properties.
[0025] This material has unlimited potential in the field of energy storage, providing a reliable and efficient solution for energy storage. Its high specific capacitance means that it can store more energy, its excellent energy density ensures a long-lasting and stable power supply, and its excellent cycle stability prolongs the service life of the device, providing a solid foundation for long-lasting performance, and plays an important role in solving the problem of energy storage. The entire preparation process is relatively simple and does not require complex equipment and conditions. This makes the invention have the potential for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the X-ray diffraction pattern of the electrode material prepared in Example 1 of the present invention.
[0027] Figure 2 This is a SEM image of the electrode material prepared in Example 1 of the present invention.
[0028] Figure 3 This is the CV curve of the electrode material prepared in Example 1 of the present invention.
[0029] Figure 4 This is the CP curve of the electrode material prepared in Example 1 of the present invention.
[0030] Figure 5 This is an energy density diagram of the electrode material prepared in Example 1 of the present invention.
[0031] Figure 6 The electrode material prepared in Example 1 of the present invention is 10Ag -1 Cyclic charge and discharge diagram under current density. DETAILED DESCRIPTION
[0032] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0033] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0034] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0035] Example 1
[0036] (1) 0.3 g Zn(NO3)2.6H2O and 0.6 g Co(NO3)2.6H2O were dissolved in 50 mL deionized water, and magnetic stirring was performed for 0.5 h at a magnetic stirrer speed of 100 r / min. Then 0.3 g urea was slowly added and stirring was continued at a speed of 100 r / min for 3 h. Then 0.074 g ammonium fluoride (NH4F) was slowly added and stirring was continued for 2 h to obtain a mixed solution.
[0037] (2) The 20×20 mm nickel foam and the mixed solution were transferred to a stainless steel autoclave (100 mL) lined with polytetrafluoroethylene (PTFE) and subjected to a hydrothermal reaction at 130°C for 5 h. The nickel foam was then taken out and placed in an oven at 130°C for reaction for 6 h. After the reaction was completed, the nickel foam was collected, rinsed with deionized water and ethanol three times in sequence, and dried in a vacuum drying oven at 80°C for 12 h. After drying, the nickel foam was placed in a muffle furnace, heat treated at 350°C for 2 h, and then naturally cooled to room temperature to obtain a ZnCo2O4 loaded nickel foam.
[0038] (3) 1.2 g Ni(NO3)2.6H2O and 0.75 g urea were added to distilled water and magnetically stirred for 0.5 h at a magnetic stirrer speed of 100 r / min. Then, the mixture and the loaded ZnCo2O4 nickel foam obtained in step (2) were transferred to a reactor and subjected to a secondary hydrothermal reaction at 120°C for 3 h. After the reaction was completed, the sample was collected and rinsed with deionized water and ethanol for 5 times in sequence. The sample was placed in a drying oven and dried at 80°C for 12 h. After drying, an electrode material was obtained, which was recorded as ZnCo2O4@NiOOH nanosheet electrode material.
[0039] The experimental results of the ZnCo2O4@NiOOH nanosheet electrode material prepared in Example 1 of the present invention are as follows.
[0040] Figure 1 The X-ray diffraction pattern of the electrode material prepared in Example 1 is given as follows: Figure 1 As shown, ZnCo2O4 and NiOOH phases can be observed, indicating that the ZnCo2O4@NiOOH nanosheet electrode material can be successfully prepared by the method of the present invention.
[0041] Figure 2 The SEM image of the electrode material prepared in Example 1 of the present invention is given, from which it can be seen that the particle size distribution of the ZnCo2O4@NiOOH nanosheet electrode material is relatively uniform.
[0042] The electrode material prepared in Example 1 of the present invention is used in a supercapacitor, and the supercapacitor is an asymmetric supercapacitor. The preparation process is as follows:
[0043] The activated carbon, acetylene black and polytetrafluoroethylene were uniformly mixed in a mass ratio of 6:3:1 to prepare the negative electrode, and then the ZnCo2O4@NiOOH electrode material was used as the positive electrode, and the PVA-KOH gel was used as the electrolyte. The prepared positive and negative electrodes were separated by a separator, and finally encapsulated with an aluminum-plastic film. The electrochemical properties of the ZnCo2O4@NiOOH nanosheet electrode material were then measured. The results are as follows Figure 3 , Figure 4 and Figure 5 shown. Figure 3 The CV curve of the electrode material prepared in Example 1 of the present invention is given. It can be seen from the figure that with the increase of the scanning rate, the oxidation peak and the reduction peak of the composite electrode CV curve of the ZnCo2O4@NiOOH nanosheet electrode material move in the positive and negative directions respectively, and the distance of the redox peak moving to the left and right is small, maintaining the same shape without distortion, indicating that the prepared ZnCo2O4@NiOOH nanosheet electrode material can maintain good rate performance and good reversible performance.
[0044] Figure 4This is the CP curve of the electrode material prepared in Example 1 of the present invention. It can be seen from the figure that as the charge and discharge current density increases, the ZnCo2O4@NiOOH nanosheet electrode material still has a high mass specific capacitance and specific capacity retention rate, the capacitor has good stability, and the service life of the supercapacitor is effectively extended.
[0045] Figure 5 This is an energy density diagram of the electrode material prepared in Example 1 of the present invention. It can be seen from the diagram that the electrode material prepared in Example 1 of the present invention has a good energy density.
[0046] Figure 6 The electrode material is shown in 10Ag -1 Cyclic charge-discharge diagram under current density. After 6000 cycles, the capacitance of the ZnCo2O4@NiOOH nanosheet electrode material maintained 89.88% of the initial capacitance, indicating that it has good service life and stability.
[0047] Example 2
[0048] (1) 0.3 g Zn(NO3)2.6H2O and 0.6 g Co(NO3)2.6H2O were dissolved in 50 mL deionized water, and magnetic stirring was performed for 0.5 h at a magnetic stirrer speed of 120 r / min. Then, 0.3 g urea was slowly added and stirring was continued at a speed of 120 r / min for 2 h. Then, 0.074 g ammonium fluoride (NH4F) was slowly added and stirring was continued for 2.5 h to obtain a mixed solution.
[0049] (2) The 20×20 mm nickel foam and the mixed solution were transferred to a stainless steel autoclave (100 mL) lined with polytetrafluoroethylene (PTFE) and subjected to a hydrothermal reaction at 200°C for 4 h. The mixture was then taken out and placed in an oven at 150°C for reaction for 5 h. After the reaction was completed, the nickel foam was collected, rinsed with deionized water and ethanol for 5 times in sequence, and dried in a vacuum drying oven at 60°C for 24 h. After drying, the nickel foam was placed in a muffle furnace and heat treated at 300°C for 4 h. The nickel foam was then naturally cooled to room temperature to obtain a ZnCo2O4 loaded nickel foam.
[0050] (3) 1.2 g Ni(NO3)2.6H2O and 0.75 g urea were added to distilled water and magnetically stirred at a magnetic stirrer speed of 120 r / min for 1 h. Then, the nickel foam loaded with ZnCo2O4 obtained in step (2) was transferred to a reactor and subjected to a secondary hydrothermal reaction at 180°C for 2 h. After the reaction was completed, the sample was collected and rinsed with deionized water and ethanol several times, and placed in a drying oven at 90°C for 12 h. After drying, an electrode material was obtained, which was recorded as ZnCo2O4@NiOOH nanosheet electrode material.
[0051] Example 3
[0052] (1) 0.3 g Zn(NO3)2.6H2O and 0.6 g Co(NO3)2.6H2O were dissolved in 50 mL deionized water, and magnetic stirring was performed at a magnetic stirrer speed of 90 r / min for 1 h. Then, 0.3 g urea was slowly added and stirring was continued at a speed of 90 r / min for 3 h. Then, 0.3 g ammonium fluoride (NH4F) was slowly added and stirring was continued for 2 h to obtain a mixed solution.
[0053] (2) The 20×20 mm nickel foam and the mixed solution were transferred to a stainless steel autoclave (100 mL) lined with polytetrafluoroethylene (PTFE) and subjected to a hydrothermal reaction at 100°C for 8 h. The mixture was then taken out and placed in an oven at 120°C for reaction for 8 h. After the reaction was completed, the nickel foam was collected, rinsed with deionized water and ethanol for 4 times, placed in a vacuum drying oven at 90°C, and dried for 12 h. After drying, the nickel foam was placed in a muffle furnace, heat treated at 500°C for 2 h, and then naturally cooled to room temperature to obtain a ZnCo2O4 loaded nickel foam.
[0054] (3) 1.2 g Ni(NO3)2.6H2O and 0.99 g urea were added to distilled water and magnetically stirred for 0.5 h at a magnetic stirrer speed of 90 r / min. Then, the nickel foam loaded with ZnCo2O4 obtained in step (2) was transferred to a reactor and subjected to a secondary hydrothermal reaction at 100°C for 4 h. After the reaction was completed, the sample was collected and rinsed with deionized water and ethanol several times, and dried in a drying oven at 70°C for 15 h. After drying, an electrode material was obtained, which was recorded as ZnCo2O4@NiOOH nanosheet electrode material.
[0055] When the ZnCo2O4@NiOOH nanosheet electrode materials prepared according to Examples 2 and 3 of the present invention were subjected to X-ray diffraction, it was also possible to observe clearly separated ZnCo2O4 and NiOOH phases. From the SEM images of the two, it can be seen that the electrode materials prepared in Examples 2 and 3 present particles of uniform size. In addition, for super electrical appliance testing, it also has high specific capacitance, good energy density and excellent cycle stability. Compared with Example 1, the electrode material prepared in Example 2 has a higher specific capacitance than that in Example 1 at 10Ag. -1 After 6000 cycles at the current density, the capacitance of the ZnCo2O4@NiOOH nanosheet electrode material maintained 87.93% of the initial capacitance; compared with Example 1, the electrode material prepared in Example 3 maintained 87.93% of the initial capacitance at 10Ag. -1 After 6000 cycles at the same current density, the capacitance of the ZnCo2O4@NiOOH nanosheet electrode material retained 88.76% of the initial capacitance.
[0056] Comparative Example 1
[0057] The difference between this comparative example and Example 1 is that the steps for preparing the ZnCo2O4@NiOOH nanosheet electrode material are different, and the rest is the same as Example 1.
[0058] The preparation method of the electrode material of this comparative example comprises the following steps:
[0059] 0.3g Zn(NO3)2.6H2O, 0.6g Co(NO3)2.6H2O, 1.2g Ni(NO3)2.6H2O, 1.05g urea and 0.074g NH4F were dissolved in deionized water, and then 20×20mm nickel foam was added and transferred to a reactor for hydrothermal reaction at 120°C for 8h. After the reaction was completed, the sample was collected and rinsed with deionized water and ethanol for 5 times in turn, and placed in a drying oven for drying at 80°C for 12h. After drying, the electrode material was obtained, which was recorded as ZnCo2O4@NiOOH nanosheet electrode material.
[0060] When the ZnCo2O4@NiOOH nanosheet electrode material of this comparative example is subjected to X-ray diffraction, ZnCo2O4 and NiOOH phases can also be observed, but the characteristic peak position is offset, and other impurity diffraction peaks appear. The microscopic morphology of the electrode material of this comparative example is observed using an electron scanning microscope, and the particles show uneven distribution of size. In addition, when used for super electrical appliance testing, the specific capacitance, energy density and cycle stability are significantly weakened. Compared with Example 1, the electrode material prepared in Comparative Example 1 has a 10Ag -1 After 6000 cycles at the current density, the capacitance of the ZnCo2O4@NiOOH nanosheet electrode material maintained 56.74% of the initial capacitance. This indicates that the ZnCo2O4@NiOOH nanosheet electrode material prepared by the method of the present invention has the characteristics of high specific capacitance, good energy density and excellent cycle stability, making it an ideal energy storage device, and the prepared supercapacitor has good specific capacitance and excellent pseudocapacitance properties.
[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an electrode material, characterized in that: The following steps are involved: (1) Add zinc nitrate and cobalt nitrate to a solvent, perform magnetic stirring for 0.5 to 1 hour, then slowly add urea and continue stirring for 2 to 3 hours, then slowly add ammonium fluoride and continue stirring for 2 to 3 hours to obtain a mixed solution; the stirring rate is 90 to 120 r / min; the molar ratio of the zinc nitrate, cobalt nitrate, urea and ammonium fluoride is 1 to 5:1 to 5:1 to 10:0 to 10; the solvent is deionized water, and the total mass of the zinc nitrate, cobalt nitrate, urea and ammonium fluoride and the volume of the solvent are in a ratio of 1.0 to 2.0 g:50 mL; (2) adding the nickel foam and the mixed solution into a reactor and performing a hydrothermal reaction at a temperature of 100-200°C for 2-10 hours, then taking out and placing in an oven for reaction, collecting the nickel foam after the reaction is completed, washing, drying, and heat treating at a temperature of 300-600°C for 2-10 hours to obtain a nickel foam loaded with ZnCo2O4; (3) Add nickel nitrate and urea to distilled water and stir magnetically for 0.5-1 h. Then add the loaded ZnCo2O4 nickel foam in step (2) to the reactor and carry out a secondary hydrothermal reaction at a temperature of 50-200°C for 2-4 h. After the reaction is completed, wash and dry to obtain an electrode material, which is recorded as ZnCo2O4@NiOOH nanosheet electrode material. The stirring rate is 90-120 r / min. The mass ratio of nickel nitrate, urea and distilled water is 1:1-5:40-60.
2. The method for preparing an electrode material according to claim 1, characterized in that: The size of the nickel foam is 15-30 mm×15-30 mm.
3. The method for preparing an electrode material according to claim 1, characterized in that: In step (2) and step (3), the cleaning solvents are deionized water and anhydrous ethanol, and the number of cleaning times is 3 to 6 times; the drying temperature is 60 to 90° C., and the drying time is 12 to 24 hours.
4. The method for preparing an electrode material according to any one of claims 1 to 3, characterized in that: An electrode material prepared by the preparation method according to any one of claims 1 to 3, and use of the electrode material in the preparation of a supercapacitor.
Citation Information
Patent Citations
Preparation method of ternary compound electrode material
CN108565133A
NiGa-LDH (at) ZnCo2O4 (at) NF composite material and preparation method and application thereof
CN114300273A